2018
DOI: 10.3390/app8112026
|View full text |Cite
|
Sign up to set email alerts
|

Au Tip-Enhanced Raman Spectroscopy for Catalysis

Abstract: Plasmon-driven chemical reactions have been a prospective field for surface plasmon resonance and tip-enhanced Raman scattering. In this review, the principles of tip-enhanced Raman spectroscopy (TERS) are first introduced. Following this, the use of Au TERS for plasmon-driven synthesis catalysis is introduced. Finally, the use of Au TERS for catalysis of dissociation reactions is discussed. This review can provide a deeper understanding of Au TERS for plasmon-driven catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 85 publications
(103 reference statements)
0
6
0
Order By: Relevance
“…Raman spectroscopy is also made great contributions to the study of TE materials [103]. With the increasing technical requirements, Raman spectroscopy has now developed into multiple branches, e.g., resonance Raman spectroscopy, surface enhanced Raman spectroscopy [104,105], tip enhanced Raman spectroscopy [106], and micro Raman spectroscopy etc. Micro-Raman spectroscopy is one of the most important techniques to characterize nanomaterials, which can identify the number of layers of film materials [107], analyze the vibration modes of 2D materials in diverse case [71], and measure the thermal conductivity [22,108,109,110].…”
Section: Raman Techniquementioning
confidence: 99%
“…Raman spectroscopy is also made great contributions to the study of TE materials [103]. With the increasing technical requirements, Raman spectroscopy has now developed into multiple branches, e.g., resonance Raman spectroscopy, surface enhanced Raman spectroscopy [104,105], tip enhanced Raman spectroscopy [106], and micro Raman spectroscopy etc. Micro-Raman spectroscopy is one of the most important techniques to characterize nanomaterials, which can identify the number of layers of film materials [107], analyze the vibration modes of 2D materials in diverse case [71], and measure the thermal conductivity [22,108,109,110].…”
Section: Raman Techniquementioning
confidence: 99%
“…Over the years more and more functionality has been developed and built-in to commercial systems and there are now a large number of imaging modes beyond the standard contact mode, tapping mode and force distance spectroscopy that have increased the power of this technique. Indeed with the development of high-speed AFM [18,19], imaging modes such as TREC [20][21][22], Peakforce tapping mode [23,24], calibration procedures to precisely quantify force [25][26][27][28] and tip shape [29,30] as well as combining AFM with other types of microscopy [31][32][33][34] this technique will continue to develop and demonstrates considerable promise into the future. However, what remains consistent in the acquisition of AFM 2 of 15 data is that the resolution and measurement accuracy of that data is strongly dependant on the AFM tip diameter, shape and durability.…”
Section: Introductionmentioning
confidence: 99%
“…Surface-enhanced Raman scattering (SERS) and tip-enhanced Raman spectroscopy (TERS) are widely used in the fields of physics, chemistry, biology, medicine, and materials, and they are highly sensitive molecular-detection tools that play a significant role in research on the electronic structure and spectral properties of molecules and plasmon-driven chemical reactions [1][2][3][4][5][6][7][8][9]. Recently, we studied the physical mechanism of plasmon-enhanced resonance Raman and fluorescence spectra [10] to understand the applications and principles of photoinduced charge transfer [11].…”
Section: Introductionmentioning
confidence: 99%
“…A lot of research shows that conversion of 4-nitrobenzenethiol (4NBT) and p-aminothiophenol (PATP) to 4,4 -dimercaptoazobenzene (DMAB) via reduction and oxidation reactions was achieved with SERS technology [2][3][4][5][6][7][8][9][10][11][14][15][16][17][18]. Theoretical and experimental studies showed that SERS synthesis of DMAB from PATP is achieved via the selective catalytic coupling of Ag nanoparticles (Ag NPs).…”
Section: Introductionmentioning
confidence: 99%